2020
DOI: 10.1029/2019jb019039
|View full text |Cite
|
Sign up to set email alerts
|

The Near‐Fault Ground Motion Characteristics of Sustained and Unsustained Free Surface‐Induced Supershear Rupture on Strike‐Slip Faults

Abstract: The free surface is shown to be one of the key factors that may promote supershear rupture propagation on strike‐slip faults even if its initial shear stress is not larger enough as predicted by the Burridge‐Andrews mechanism. However, previous study has shown the free surface‐induced supershear rupture may be unsustained, which turns to sub‐Rayleigh rupture itself as the rupture propagates. We study the near‐field ground motion of sustained and unsustained supershear ruptures using the finite difference metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 54 publications
1
15
0
Order By: Relevance
“…To obtain a better understanding of ground motion characteristics of the three rupture scenarios, Figure 5 compares the particle velocities and their normalized frequency amplitudes at five stations with a 1 km interval spanned along the FN direction (Figure 1). For the Scenario A (Figure 5a), the strong peak FP peaks arrive earlier than the weaker FN peaks, which is a distinguishing feature of supershear feature (Aagaard & Heaton, 2004; Hu et al., 2020). The shear and Rayleigh Mach fronts can be seen in both the FP and FN components, although the time differences between the shear and Rayleigh arrivals are small.…”
Section: Resultsmentioning
confidence: 96%
“…To obtain a better understanding of ground motion characteristics of the three rupture scenarios, Figure 5 compares the particle velocities and their normalized frequency amplitudes at five stations with a 1 km interval spanned along the FN direction (Figure 1). For the Scenario A (Figure 5a), the strong peak FP peaks arrive earlier than the weaker FN peaks, which is a distinguishing feature of supershear feature (Aagaard & Heaton, 2004; Hu et al., 2020). The shear and Rayleigh Mach fronts can be seen in both the FP and FN components, although the time differences between the shear and Rayleigh arrivals are small.…”
Section: Resultsmentioning
confidence: 96%
“…Hu et al. (2019, 2020) have shown that the existence of a daughter crack in strike‐slip faults cannot guarantee a sustained supershear rupture, since the daughter crack is possible to be absorbed by the following main crack, which turns into an unsustained supershear rupture. Our simulations show even if the “supershear” (in the 1D gradient view) daughter crack can propagate to the fault bottom, its near field ground motion could still present sub‐Rayleigh characteristics as revealed in the 2D gradient.…”
Section: Discussionmentioning
confidence: 99%
“…Our interpretation, in contrast, is that the diagonal rupture fronts are a consequence of the supershear rupture right at the surface leading the subshear rupture at depth; the diagonal rupture fronts in our interpretation are a symptom, rather than a cause, of the subshear rupture at depth. Hu et al (2019Hu et al ( , 2020 have shown that the existence of a daughter crack in strike-slip faults cannot guarantee a sustained supershear rupture, since the daughter crack is possible to be absorbed by the following main crack, which turns into an unsustained supershear rupture. Our simulations show even if the "supershear" (in the 1D gradient view) daughter crack can propagate to the fault bottom, its near field ground motion could still present sub-Rayleigh characteristics as revealed in the 2D gradient.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations